Peningkatan Pengetahuan tentang Senam Desminorea untuk Mengurangi Nyeri pada Siswa SMA di Kota Denpasar - Ni Komang Tri Agustini; Ida Ayu Ningrat Pangruating Diyu (Jurnal Pengabdian Pada Masyarakat, 2019)
INCREASED KNOWLEDGE ABOUT DESMINOREA GYMNASTICS TO REDUCE PAIN IN HIGH SCHOOL STUDENTS IN DENPASAR CITY. Menstrual pain or dysmenorrheal is a physical disorder that is often felt by women every menstruation. Dysmenorrheal is often reported to interfere with daily activities. The incidence of dysmenorrheal shows that the experience of dysmenorrheal is mostly experienced by adolescents, including adolescent in high school. To reduce the menstrual pain every menstruation requires sufficient knowledge and understanding of the actions that can be done to reduce menstrual pain, one of them is dysmenorrheal exercises. This activity aims to provide education about dysmenorrheal exercises used to reduce menstrual pain. The method used is to provide health education about menstrual pain and training about dysmenorrheal exercise. Before and after counseling pre test and post test. The results of counseling showed an increase in teenagers understanding of dysmenorrheal exercise to reduce menstrual pain, from 52.5% to 80%. Based on these results it is expected that teenagers are able to practice dysmenorrheal exercises to reduce menstrual pain.